Outcomes of endoscopic submucosal dissection (ESD) during live endoscopy events (LEE) – a 13-year follow-up - Ebigbo, Alanna; Freund, Simone; Probst, Andreas; Römmele, Christoph; Gölder, Stefan K.; Frauenschuh, Julia; Marienhagen, Joerg; Messmann, Helmut (Endoscopy International Open, 2019)
Background and study aims There are no data showing the outcome of ESD during live endoscopy events (LEE). ESD performed during the Augsburg Endo-Update LEE were compared with matched routine procedures with the aim of demonstrating non-inferiority of LEE ESD.Patients and methods ESD performed during the Endo-Update between 2006 and 2018 were reviewed. The controls were routine procedures matched according to age, location and lesion size. Resection, recurrence, survival and complication rates, procedure time and propofol sedation were assessed. Clinically relevant margins were assumed for resection and complication rates, procedure time and propofol sedation quantity.Results Thirty-eight ESD were performed in the given time period, and were compared with 38 matched routine ESD. En bloc and curative resection rates in the LEE group and in the control group were 100 % and 87 % as well as 84 % and 71 % respectively, while procedure times were 135 and 125 minutes, respectively. Non-inferiority was demonstrated for resection rates and procedure time. The complication rate was lower in the LEE group as compared with the control group (5 % vs 13 %) while propofol sedation was similar in both groups (863 mg vs 872 mg). Recurrence and 5-year survival rates for both groups were 4 % vs 0 % and 70 % vs 65% respectively.Conclusions The resection rate and procedure time of ESD during LEE was non-inferior to those of routine ESD procedures. Comparison of the complication rates, however, was inconclusive owing to the low patient number and complication risk in both groups.